Protonska radiografija - Levpušček, Blaž (Matrika, 2021)
The article describes proton radiography - a way of imaging the human body with protons which gives us an accurate image of their stopping depth. The dose left in the human body is lower than that left from X-ray imaging. In this article the basic physical mechanisms of proton radiography are presented, as well as expected standards that this technology needs to meet to become mainstream.
Keywords: medical imaging; medical physics; medicinska fizika; medicinsko slikanje; proton radiography; protonska radiografija